Photodynamic antitumor activity of tetrahydroxyl-methyl pyropheophorbide-a with improved water-solubility and depth of treatment. (November 2022) - Zhang, Ying; Chen, Siyang; Xia, Qing; Zhang, Hui; Wang, Zhiqiang; Yan, Rui; Zhang, Xu; Dai, Jingping; Wu, Xiaodan; Fang, Wen; Jin, Yingxue
Abstract: Methyl pyropheophorbide-a (MPPa) is a chlorophyll degradation product that possesses excellent photophysical and photochemical properties, yet poor water solubility limits its clinical application. In this paper, a novel MPPa derivative, 3 1, 3 2, 7, 8-tetrahydroxy-4 H-MPPa (HMPPa) was synthesized by oxidative hydrolysis of MPPa with potassium osmate. The four hydrophilic hydroxyl groups endow HMPPa with better water solubility (lipid water partition coefficient logP = −0.16), which solve the problem of MPPa aggregation in water. HMPPa has a long-wavelength near-infrared absorption at 740 nm that can achieve a deeper penetration depth in biological tissues, which allows HMPPa to be applied in deep tumor therapy. Moreover, HMPPa possesses a higher singlet oxygen quantum yield (62.65 %) than that of MPPa (56 %). MTT assay verified that HMPPa had a strong ability to inhibit the growth of HepG-2 cells and 4T1 cells, and the PDT effect was superior to that of MPPa. Cell morphology experiments and flow cytometry analysis showed that HMPPa could induce apoptosis via a mitochondrial pathway. In vivo study of HMPPa showed a significant PDT antitumor effect on 4T1 tumor-bearing mice (Balb/C). The tumor cells followed by treatment of HMPPa could be clearly observed under fluorescence microscopy, implying a good fluorescence imaging function of HMPPa. Graphical Abstract: Synthesis and Antitumor effect by PDT of 3 1, 3 2, 7, 8-tetrahydroxy-4 H pyropheophorbide-a methyl ester (HMPPa). ga1